Factors Influencing The Formation of Entrepreneurial Culture - Qozokov Sobirjon Zokirjonovich (Indonesian Journal Publisher, 2026)
The article provides a socio-analytical examination of the factors influencing the formation of entrepreneurial culture. In analyzing entrepreneurial culture, the author makes extensive use of scholarly literature from foreign countries and, through its critical review, identifies key factors shaping entrepreneurial culture in international contexts. At the same time, particular attention is paid to the factors contributing to the formation of entrepreneurial culture in Uzbekistan under conditions of ongoing reforms. The article also elucidates the role of entrepreneurial culture in societal development, revealing the factors that influence its formation through the example of the entrepreneur as a social actor. On this basis, the main tasks involved in fostering entrepreneurial culture are systematically analyzed. In addition, the author proposes an original definition of the concept of entrepreneurial culture and examines its institutional foundations.